Drinking water policy, water rights and allocation practice in rural Northern Ghana - Irit Eguavoen (2008)
Rural drinking water policy in Ghana is based on the ´communal management´ approach. The formal membership in water user communities has been introduced in the end 1990s during the implementation of a new water policy, called National Community Water and Sanitation Program. Members of pump communities hold a monopoly on ownership, access and power over their water facility. But local water users also had to balance contradictions and conceptual differences between their previous water right regime and innovative institutions. Despite a new conceptual design, structural shifts in the pattern of water user groups and the local diversification of water rights and rules, the practice of household water allocation does not show major changes but continues to depend primarily on non- institutional factors.